2014
DOI: 10.1260/2040-2295.5.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Safety Measurements for Heating of Instruments for Cardiovascular Interventions in Magnetic Particle Imaging (MPI) ‐ First Experiences

Abstract: Magnetic particle imaging (MPI) has emerged as a new imaging method with the potential of delivering images of high spatial and temporal resolutions and free of ionizing radiation. Recent studies demonstrated the feasibility of differentiation between signal-generating and non-signal-generating devices in Magnetic Particle Spectroscopy (MPS) and visualization of commercially available catheters and guide-wires in MPI itself. Thus, MPI seems to be a promising imaging tool for cardiovascular interventions. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
0
19
1
Order By: Relevance
“…First results towards real time MPI were already presented recently by Salamon et al [55]. For MPI-guided interventions the safety of devices like guide wires and stents also has to be considered [56]. …”
Section: Discussionmentioning
confidence: 99%
“…First results towards real time MPI were already presented recently by Salamon et al [55]. For MPI-guided interventions the safety of devices like guide wires and stents also has to be considered [56]. …”
Section: Discussionmentioning
confidence: 99%
“…They presented the feasibility of MPI of SPIOs labeled endovascular instruments at high temporal resolution [ 6 ] and introduced the first magnetic coating of interventional devices for MPI visualization with a coating thickness of about 500 μm [ 13 ]. Various interventional instruments have been investigated concerning potential heating in MPI [ 7 ]. For our study we used instruments that showed neither heating nor artifacts in MPI.…”
Section: Discussionmentioning
confidence: 99%
“…Potential MPI utilizations include cardiovascular applications (angiographies, cardiac vitality evaluation, tissue perfusion, plaque labeling, endovascular interventions, detection of bleeding sources) or applications in tumour, molecular, and cellular imaging (passive and active targeting, molecular therapies, cellular labeling and cell monitoring) [ 5 ]. For the broad sector of potential interventional applications, as therapeutic endovascular or thermoablative approaches, Haegele et al demonstrated promising results in initial experimental studies [ 6 ], although potential heating of the material has to be considered [ 7 ] and labelling of endovascular devices has to be optimized. For in-vivo MPI of interventional instruments currently two strategies are pursued.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the theranostic potential of MPI extends far beyond guiding cell-based treatments. Although this review focuses on MPI imaging applications, extensive work has also been performed demonstrating the utility of MPI for ionizing radiation-free surgical guidance 3437 and therapeutic guidance, such as with magnetic hyperthermia 3842 .…”
Section: Cell Trackingmentioning
confidence: 99%